(untitled) (International relations and international law Journal, 2018)
This article analyzes the problem of information security of the Republic of Kazakhstan, which is urgent today, under the influence of the Russian mass media. The authors examine that impact directly within the context of different events of bilateral relations between states, as well as international ones, directly or indirectly affecting the relations between Kazakhstan and Russia. The relevance of this topic is related primarily to the strengthening of information warfare between Ukraine and Western countries, on the one side, and Russia on the other side. The article focuses on the analysis of features of information security and its provision of both states. The article presents the basic problems of information security in this context. In conclusion, the authors show the ways of solving these problems. Key words: information security; mass media influence; information warfare; protection of information space.